A Planar V-Band Antenna for Wideband Radar and Communication on Low-Cost PCB Substrate - Peters, Sebastian; Faghih-Naini, Samira; Erhardt, Stefan; Reißland, Torsten; Weigel, Robert (IEEE Radio and Wireless Symposium (RWS), 2023)
A rectangular microstrip antenna with a resonant frequency of 60.5 GHz and a bandwidth of 4 GHz is proposed and evaluated. The antenna is based on the low-cost substrate RO4350B and is designed to reduce costs for prototypes and small batch series by complying with design restrictions for inexpensive pooling offers by many manufacturers. The influence of manufacturing tolerances on the performance of the antenna is also investigated and minimized. Finally, an antenna is fabricated and measurements are compared with simulation

Bringing Portability to a New Level: A High-Sensitivity, Low-Power Monostatic CW Radar at 24 GHz - Peters, Sebastian; Horlbeck, Marie; Probst, Florian; Weigel, Robert (IEEE Microwave Magazine, 2022)
Radar technology offers unique advantages that distinguish it from conventional sensing technologies. Now, research on industrial sensor systems is rapidly increasing. Due to the massive integration of RF circuits in monolithic microwave integrated circuits in recent years, radar systems can be designed to be very compact, inexpensive, and at the same time, feature a low power consumption [1] , [2] . This development is also pushed by the digital transformation of production in various industries, commonly known as the fourth industrial revolution [3] , [4] . In industrial environments, radar technology offers various advantages over conventional sensors. The combination of high resolution, low power consumption, and operation in harsh environments makes radar sensors extremely attractive. Additionally, radar technology also stands out from other sensor technologies in the medical field. Radar systems can be used for simple presence monitoring or, due to the very high resolution, for gesture recognition or even for recording vital parameters. Minimal movements on the surface of the chest caused by respiration or heartbeat are strong enough to be detected by radar systems without contact [5] , [6] .<br

Combining an FMCW radar system with FSK modulation to a joint communication and sensing system - Faghih-Naini, Samira; Schneider, Michael; Peters, Sebastian; Weigel, Robert; Reißland, Torsten (International Journal of Microwave and Wireless Technologies, 2025)
Due to the rising occupancy of the radio spectrum, new strategies for covering the ever increasing amount of data are necessary. This work presents a system for integrating data transmission into a frequency-modulated continuous wave (FMCW) radar by modulating the radar signal with frequency shift keying (FSK). The system offers a high chirp bandwidth of 5 GHz and uses the 60 GHz band. The FSK carrier frequency affects the noise level. A higher frequency leads to a lower noise floor due to 1/f-noise but requires a higher sampling rate. Therefore, 15 MHz was chosen as a compromise. A high data rate allows for a fast data transmission but requires a short chirp time, which leads to a noisier frequency chirp. The radar parameters are also affected by this choice. This leads to a baud rate of 20.8 kbit/s. With a higher order FSK, higher data rates are possible. This proves that the data transmission via FMCW radar signals is possible and a first choice if lower data rates are sufficient, because the hardware effort is comparatively low.
CRIS-Team Scopus Importer:2025-05-16
Keywords: digital signal processing; frequency shift keying; millimeter wave communication; millimeter wave radar

Design and Evaluation of a Joint Communication and Sensing System Using FMCW-Radar and FSK in V-Band - Faghih-Naini, Samira; Peters, Sebastian; Kurin, Thomas; Reißland, Torsten; Weigel, Robert (20th European Radar Conference (EuRAD 2023), 2023)

FPGA Based Evaluation Platform for High Performance Digital mmWave Radar Systems - Peters, Sebastian; Faghih-Naini, Samira; Erhardt, Stefan; Weigel, Robert; Reißland, Torsten (Asia-Pacific Microwave Conference (APMC), 2024)
An evaluation platform for digital radar systemsoperating at 60 GHz is proposed and demonstrated. With a sampling rate of 4 GSa/s, a range resolution of below 4 cm can be achieved. The transmit sequence can be up to 2^18 samples long, leading to a possible unambiguous range of more than 9 km. The platform is designed for offline signal processing for maximum flexibility, meaning that data rates in excess of 100 Gbit/s are handled to both play back and record data during measurement.<br
Keywords: digital signal processing; field programmable gate arrays; millimeter wave radar; radar signal processing; system validation

Improved Performance in PMCW Radar Systems Through Equalization Using Predistortion and Postprocessing - Peters, Sebastian; Faghih-Naini, Samira; Weigel, Robert; Reißland, Torsten (IEEE MTT-S International Microwave Symposium Digest, 2024)
This work presents multiple concepts for spectral equalization in pulse-modulated continuous wave (PMCW) radar systems in order to restore the received signal for improved correlation results. Two concepts for postprocessing are presented which use the spillover signal for calibration. A third concept is introduced which uses a predistorted transmit signal and thus does not require spectral equalization in the receiver. The concepts are verified through measurements using a 60 GHz transceiver together with digital-to-analog converters (DACs) and analog-to-digital converters (ADCs) operating at 4 GSa/s, resulting in a range resolution of under 4 cm.
CRIS-Team Scopus Importer:2024-08-16
Keywords: digital signal processing; millimeter wave radar; predistortion; radar signal processing

Low-Cost and High Performance Antenna Setup for Updating ePaper Displays on Curved RFID SmartTags Used in Pharmaceutical Studies - Peters, Sebastian; Hangmann, Christian; Wüllner, Ingo; Traupe, Joschka; John, Tobias; Weigel, Robert; Scheiner, Benedict (IEEE MTT-S International Microwave Symposium Digest, 2023)
This work presents a scalable RFID antenna setup used to update passive SmartTags mounted on round containers. Examples where this technology can be highly beneficial are pharmaceutical studies. The reader antennas are placed under the containers and are designed to ensure RFID communication and power transfer independent of container rotation with multiple containers in close proximity. The effects of the proposed antenna setup on the system are analyzed both theoretically and in simulations. Measurements are performed to verify the results and to demonstrate the system.
CRIS-Team Scopus Importer:2023-09-01
Keywords: antenna arrays; HF antennas; medical information systems; RFID tags; smart healthcare; smart transportation

Transceiver Setup for Joint Communication and Sensing Applications in V-Band - Faghih-Naini, Samira; Peters, Sebastian; Kurin, Thomas; Erhardt, Stefan; Reißland, Torsten; Weigel, Robert (IEEE Radio and Wireless Symposium (RWS), 2023)
A new transceiver setup for joint communication and sensing (JCAS) application in V-band with a 3 dB bandwidth of 2.57GHz is presented in this work. With new communication standards like 6G and a rising amount of wireless transmitted data, new transceiver setups for higher carrier frequencies and larger bandwidth need to be developed. The new transceiver setup has differential IQ input ports and a carrier frequency ranging from 57 GHz to 64 GHz. For the proof of radar and communication applications, the reflected IQ signal was detected, and the usability confirmed. This setup can be used for JCAS applications in meter range with high resolution and data rates. <br
Keywords: millimeter wave circuits; millimeter wave communication; millimeter wave radar; transceiver

Validation of a 4-Port and 3-Port Rat-Race Balun for the 60 GHz- Band - Faghih-Naini, Samira; Peters, Sebastian; Reißland, Torsten; Weigel, Robert (LASCAS 2024 - 15th IEEE Latin American Symposium on Circuits and Systems, Proceedings, 2024)
This work presents a rat-race coupler as a balun for the 60 GHz-band. To simplify the structure, also the 3-port rat-race balun is also simulated and manufactured to compare these two balun types. They were analyzed with a vector network analyzer (VNA) and show in the frequency range of 58 GHz to 63 GHz a maximum insertion loss of 3.5 dB and 3.9 dB, respectively and a return loss of 10 dB or less. The common mode rejection ratio (CMRR) is better than 17 dB. The insertion loss and the return loss can further be improved within a measurement setup with connectors with less reflections. It was shown that a 3-port rat-race balun is a valid alternative and has advantage in size and complexity over marchand baluns or substrate integrated waveguide (SIW) baluns.
CRIS-Team Scopus Importer:2024-05-17
Keywords: 60 GHz-band; microstrip balun; milimeter wave; rat-race